1995
DOI: 10.1007/bf02576780
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy decreases cancer colonic cell adhesiveness and metastatic potential

Abstract: Plasma membrane damage induced in various cell targets by hematoporphyrin (HPD) photodynamic therapy (PDT) could modify cancer cell adhesiveness, an important parameter in cancer metastasis. We investigated the effect of HPD or HPD incubation followed by argon laser light on the adhesiveness of progressive (PROb) or regressive (REGb) cancer cells of the same colonic origin but with a different in vivo metastatic potential. Adhesiveness was studied on plastic or endothelial cell monolayers (ECM). In the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…BPD-MA PDT of fibroblast interfered with cell adhesion without altering integrin expression (Margaron et al, 1997), which is consistent with observations in our study. HPD PDT caused a reduced adhesion of colonic cancer cells to endothelial cells (Vonarx et al, 1995). Other membrane and non-membrane agents also modulate the expression of integrins (Danilov and Juliano, 1989;Conforti et al, 1990;Elices et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…BPD-MA PDT of fibroblast interfered with cell adhesion without altering integrin expression (Margaron et al, 1997), which is consistent with observations in our study. HPD PDT caused a reduced adhesion of colonic cancer cells to endothelial cells (Vonarx et al, 1995). Other membrane and non-membrane agents also modulate the expression of integrins (Danilov and Juliano, 1989;Conforti et al, 1990;Elices et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Following in vitro PDT, adhesiveness of malignant cells to EC, as well as their capability to invade the basement membrane (13) decline. Similarly, Vonarx et al (14) observed that PDT using a hematoporphyrin derivative decreased the adhesiveness of colonic cancer cells to EC monolayers. The effect of PDT was also studied on cadherins, another class of adhesion molecules primarily responsible for the formation of stable junctions between cells in tissues.…”
Section: Adhesion Moleculesmentioning
confidence: 87%
“…It has been described an effect of PDT on either decreasing or increasing adhesion to plastic, ECM and to endothelial cells [186, 190, 191]. PDT using BPD-MA inhibited cell adhesion, with no significant differences between matrices and without altering integrin expression [185].…”
Section: Morphology Cell Adhesion Cytoskeleton and Metastasesmentioning
confidence: 99%
“…Three major eukaryotic cytoskeletal proteins are actin, tubulin and intermediate filaments. Any disturbances in these systems have been related to tumor progression and metastasis [191]. Changes in the cell shape (cell attachment, cytoskeleton) in the course of apoptosis execution promote the formation of apoptotic bodies.…”
Section: Morphology Cell Adhesion Cytoskeleton and Metastasesmentioning
confidence: 99%